2018
DOI: 10.2147/rru.s166497
|View full text |Cite
|
Sign up to set email alerts
|

Colony-stimulating factors detected in tumor cells and voided urine are potential prognostic markers for patients with muscle-invasive bladder cancer undergoing radical cystectomy

Abstract: BackgroundThe clinical use of macrophage colony-stimulating factor, granulocyte colony-stimulating factor (G-CSF), and granulocyte macrophage colony-stimulating factor (GM-CSF) has improved the safety of cytotoxic chemotherapy. However, the overexpression of these CSFs in cancers has been reported to be associated with a poor prognosis in various malignancies. We evaluated the potential of CSF expression as a predictor of clinical outcome in patients with muscle-invasive bladder cancer (MIBC).MethodsConsecutiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Even if CSF1 was secreted by bladder tumor cells [ 162 , 163 ], only 34% of patients have a high expression of CSF1 in tumor tissues. Moreover, CSF1 expression was neither associated with clinicopathological features nor correlated with RFS or CSS [ 164 ]. However, CSF1 serum and urine levels of MIBC patients were higher than those of NMIBC patients and controls [ 164 ].…”
Section: Targeting Tams To Improve Bladder Cancer Outcomementioning
confidence: 99%
See 1 more Smart Citation
“…Even if CSF1 was secreted by bladder tumor cells [ 162 , 163 ], only 34% of patients have a high expression of CSF1 in tumor tissues. Moreover, CSF1 expression was neither associated with clinicopathological features nor correlated with RFS or CSS [ 164 ]. However, CSF1 serum and urine levels of MIBC patients were higher than those of NMIBC patients and controls [ 164 ].…”
Section: Targeting Tams To Improve Bladder Cancer Outcomementioning
confidence: 99%
“…Moreover, CSF1 expression was neither associated with clinicopathological features nor correlated with RFS or CSS [ 164 ]. However, CSF1 serum and urine levels of MIBC patients were higher than those of NMIBC patients and controls [ 164 ].…”
Section: Targeting Tams To Improve Bladder Cancer Outcomementioning
confidence: 99%
“…The delivered cargo system induces its immune response through stimulation of GM-CSF in Rb protein-deficient cells. GM-CSF expression typically leads to downstream granulocyte, macrophage, lymphocyte, and dendritic cell activation, which has been implicated in antitumor activity in many malignancies [82][83][84].…”
Section: Cg0070mentioning
confidence: 99%
“…Figure 2 shows representative images of IHC staining of seven immune-related markers using surgically resected UC specimens. Our previous works have presented the oncogenic or anti-tumoral effect of endogenous and exogenous colony-stimulating factors (CSFs) in UC [80][81][82]. In addition, accumulating evidence revealed that CD204, but not CD163, positive tumor-associated macrophages are associated with the aggressive behavior of various cancers including UC [16,83].…”
Section: The Immunological Profile In the Tumor Microenvironment Of Uc Arises From Different Primary Originsmentioning
confidence: 99%